Disclosure of Money Laundering Through Investigative Audit and Forensic Accounting - Dedy Sudarmadi (Program Studi Akuntansi Universitas Langlangbuana Bandung, 2022)
The aims of this study are to identify and analyze: (1) valid and effective forensic testing practices in prevention; (2) the application of valid and effective legal accounting for fraud detection. Financial statements are accounting information, one of the media that can be used by parties with an interest in the company/institution as a basis for decision making. Financial statements are actually an official statement that must be legally accounted for errors or dishonesty in the presentation of the presentation of the juridical consequences for the presenter. What is contained in the financial statements can be used as a basis for suing the presenter by parties who feel aggrieved because of trusting and using the report. Fraud is used for a variety of sinful acts: a) Fraud involving fraud to obtain unfair or illegal financial gain. b) False statement in the application of an amount or including data in accounting records or financial statements of an entity. c) Theft, whether accompanied by a false statement of accounting records or financial statements or not. The research method used is descriptive qualitative method. Determining respondents using the key person technique, namely people who work as forensic audits. The data used are primary data obtained from the results of interviews between researchers and respondents. This study uses source triangulation analysis techniques in testing the data. Based on the results of the analysis, the results of the investigative audit stages are predicate, hypothesis formulation, data collection, data testing, data analysis, summons for interviews and interrogation, calculation of losses, and reporting. Then the key is also that in theory and practice there is no investigative audit technique that is chosen as the most effective technique. Because previously the audit needs to consider the matters and characteristics of money laundering cases, only after that determines which investigative audit technique will be used. Investigative auditors give the results that the hypothesis test has been accepted, meaning that the ability of the examiner-investigator has a significant influence on the effectiveness of testing performing audit procedures in the use of money. The data analysis technique used is a quantitative method where the results are expressed in numbers. The data used is SPSS version 26 with the result that forensic audits have no effect on financial reporting, and audit investigations on financial reporting.